Effect of Torula Yeast (Candida utilis)-Derived Glucosylceramide on Skin Dryness and Other Skin Conditions in Winter - SATO, Toshiya; HAMAGUCHI, Masahide; WADA, Sayori; AOI, Wataru; FUKUNAGA, Shoko; HIGASHI, Akane (Journal of Nutritional Science and Vitaminology, 2018)
Glucosylceramide (GlcCer) is present in foods such as barley, corn, and wheat flour. GlcCer derived from different foods has differences in its physiological effects, depending on the sphingoid backbone and constituent fatty acids. In this study, we investigated the moisturizing and skin conditioning effects of GlcCer derived from torula yeast (Candida utilis) in healthy human subjects. The participants were randomly distributed in a crossover, double-blind comparative manner. Seventeen volunteers were orally administered both 1.8 mg/d of GlcCer derived from torula yeast and a placebo for 4 wk. Before and after oral administration, transepidermal water loss (TEWL) was measured and the objective skin condition observation and a questionnaire on skin condition were conducted. The primary endpoint was TEWL; secondary endpoints included the objective and subjective skin conditions. The change in TEWL over the study period on the forearm was −0.97±0.48 and −1.26±0.46 g/m2•h in the placebo and GlcCer groups, respectively, with significantly lower (p=0.01) TEWL observed in the GlcCer group. Brown spots increased in the placebo group but significantly decreased in the GlcCer group (p=0.04). Although chapped skin worsened in the placebo group, it significantly improved in the GlcCer group (p=0.04). The use of torula yeast-derived GlcCer as a functional cosmeceutical food is a viable option to ameliorate skin conditions, including improvement in skin barrier function, reduction of brown spots, and fixation of chapped skin.